Medication appropriateness tool for co‐morbid health conditions in dementia: consensus recommendations from a multidisciplinary expert panel. Issue 10 (October 2016) - Page, A. T.; Potter, K.; Clifford, R.; McLachlan, A. J.; Etherton‐Beer, C.
Abstract : Background: Medication management for people living with dementia is a complex task as it is unclear what constitutes optimal medication management in this population due to the shifting focus of health priorities and the balance between the benefits and harms of medications. Aim: This study sought expert opinion to create a consensus list to define appropriate medication management of co‐morbidities for people with dementia. Methods: This study used the Delphi technique. We invited multidisciplinary experts in geriatric therapeutics including pharmacists, doctors, nurse practitioners, a patient advocate and a psychologist to participate. Participants were asked to engage into three or more rounds of questioning. Round 1 was a questionnaire comprised of one question defining dementia and seven open‐ended questions about appropriate management of co‐morbidities in people with dementia. Two investigators qualitatively analysed the responses to questions from Round 1 using thematic analysis. The results of this analysis were provided to participants as statements in the Round 2 survey. The participants were asked to rate their agreement with each statement on a 5‐point Likert scale. The median and interquartile range (IQR) were calculated for the responses to each statement. Consensus was pre‐specified as an IQR less than or equal to 1. Statements where consensus was not achieved were presented to participants in Round 3. The Round 2 median and IQR values were provided and participants were again asked to rate their agreement with each statement on a 5‐point Likert scale. The statements where participants agreed or strongly agreed were included in the Medication Appropriateness Tool for Co‐morbid Health conditions in Dementia criteria. Results: Fifty‐seven experts agreed to participate in the study, of whom 58% were pharmacists and 36% were medical practitioners. Fifty‐five participants completed the Round 1 (95% response rate). A total of 128 statements was included in the Round 2 survey. Consensus was reached on 93 statements in Round 2 ( n = 48 responders, 84% response rate) and on 18 statements in Round 3 ( n = 43 responders, 75% response rate). The participants reached consensus on 111 of 128 statements. Of these statements, 67 statements were included in the Medication Appropriateness Tool for Co‐morbid Health conditions in Dementia criteria. The statements were in the broad themes of preventative medication, symptom management, disease progression, psychoactive medication, treatment goals, principles of medication use, side‐effects and medication reviews. Discussion: This research provides consensus‐based guidance for clinicians who manage co‐morbid health conditions in people with dementia.